The role of parvovirus B19 in the pathogenesis of autoimmunity and autoimmune disease. Issue 4 (7th December 2015) - Kerr, Jonathan R
Abstract : Human parvovirus B19 is a single-stranded DNA virus which preferentially targets the erythroblasts in the bone marrow. B19 infection commonly causes erythema infectiosum, arthralgia, fetal death, transient aplastic crisis in patients with shortened red cell survival, and persistent infection in people who are immunocompromised. Less common clinical manifestations include atypical skin rashes, neurological syndromes, cardiac syndromes, and various cytopenias. B19 infection has also been associated with development of a variety of different autoimmune diseases, including rheumatological, neurological, neuromuscular, cardiovascular, haematological, nephrological and metabolic. Production of a variety of autoantibodies has been demonstrated to occur during B19 infection and these have been shown to be key to the pathogenesis of the particular disease process in a significant number of cases, for example, production of rheumatoid factor in cases of B19-associated rheumatoid arthritis and production of anti-glutamic acid decarboxylase (GAD) in patients with B19-associated type 1 diabetes mellitus. B19 infection has also been associated with the development of multiple autoimmune diseases in 12 individuals. Documented mechanisms in B19-associated autoimmunity include molecular mimicry (IgG antibody to B19 proteins has been shown to cross react with a variety of recognised human autoantigens, including collagen II, keratin, angiotensin II type 1 receptor, myelin basic protein, cardiolipin, and platelet membrane glycoprotein IIb/IIIa), B19-induced apoptosis with presentation of self-antigens to T lymphocytes, and the phospholipase activity of the B19 unique VP1 protein.